The Role of Accounting in Encouraging Transparency and Sustainability in the Tourism Sector: A Systematic Literature Review - KARMILA, Anak Agung Istri Anom; SARI, Gusti Ayu Putu Rista Puspita; PURNAMAWATI, Ni Komang; DEWI, Gusti Ayu Made Kusuma (PT Batara Swastika Harati, 2025)
The tourism sector is one of the key drivers of economic growth, especially in developing countries like Indonesia, where it contributes significantly to employment, investment, and regional development. In response to the growing need for transparency, accountability, and sustainability, accounting plays a crucial role in strengthening governance and optimizing financial management within the tourism industry. This study aims to explore the role of accounting in supporting tourism development through a Systematic Literature Review (SLR). A total of 20 national and international scientific articles published between 2019 and 2024 were reviewed to examine the relationship between accounting practices and tourism sector growth. The findings reveal that good accounting practices can enhance financial transparency, build investor and stakeholder trust, and support the sustainability of tourism business operations. Additionally, the digitalization of accounting systems has improved reporting efficiency and managerial decision-making. These results underline the importance for tourism industry players to integrate effective accounting systems to ensure sustainable and competitive business performance.